PENGARUH KEBIJAKAN PEMBERIAN TUNJANGAN TAMBAHAN PENGHASILAN PEGAWAI (TPP) DALAM MENINGKATKAN KINERJA APARATUR (SUATU STUDI DI DINAS KOMUNIKASI DAN INFORMATIKA KOTA MANADO) - Abriando, Rizky (Universitas Sam Ratulangi, 2013)
Policy of TPP to Regional civil servants Manado City is expected to increase the performance of the apparatus. But implementation is still found weaknesses. Destination this study was to determine the effect of the policy of TPP in improving the performance of officials in the Deportment of Communication and information Monado. The method used in this study is a quantitative method. Sources of data, research respondents was 35 employees Office of Communications and informatics of Monado (no sampling). Collecting data using questionnaires and assisted with interviewing techniques. The analysis technique used is regression analysis and product moment correlation. Results of data analysis showed: (1) the regression coefficient of the variable policy of TPP to the increased performance of the apparatus is a significant positive and (2) the correlation coefficient and the coefficient of determination TPP policy variables to the increase apparatus performance is high and significant. Based on the results of these studies concluded that the policy of TPP effect and has a high power and a significant determinant of the increased performance of the apparatus. Departing from the results of the study suggested that the policy of the city of Monado Regional civil servants TPP to be continued in order to maintain and improve the performance of officials/employees. Keywords: policy, performance.